The Development of Teachers’ Pedagogical Competencies of Islamic Religious Education based on Learning Quality Management - Nurfuadi Nurfuadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article analyzed the teachers’ role of Islamic Religious Education in Madrasah, in managing learning to improve the good quality and professional learning. This method used descriptive qualitative approach by exploring the teachers in the management learning quality of three schools, for instance Madrsah Aliyah (MA) Al-Ikhsan Beji Kedung Banteng Banyumas, Madrasah Aliyah Negeri (MAN) 1 Banyumas, and MAN 2 Banyumas. The competent and smart teachers would be able to develop the students’ learning, either in a professional or responsible manner. Through pedagogical abilities, the teachers were able to independently improve the development of their knowledge by reviewing, internalizing, and realizing the output of learners competing in the education world. The researcher found that professional teachers were able to deliver the students to have a righteous attitude in both school and outside of school. Keywords: Pedagogical Competencies, Learning Quality Management, Development Pedagogical Competence